Evaluasi Perkuliahan Daring Menggunakan Metode Naive Bayes dan Post-Study System Usability Questionnaire (PSSUQ) - Fiarni, Cut; Yonata, Yosi; Romario, Romario (Yayasan Petra Harapan Bangsa, 2023)
The spread of Covid-19 to almost all countries in the world affects various aspects of human life. Through Circular Letter Number 4 of 2020 concerning the Implementation of Education Policies in the Emergency Period of the Spread of Covid-19, the government decided to change the implementation of offline learning to online learning. XYZ University in Bandung City already has a Quality Assurance Division that is tasked with evaluating the use of information technology (IT) for the offline learning process, but it also needs an IT utilization evaluation instrument related to all aspects of online learning. This research aims to create an online learning evaluation system based on international standards by considering the quality aspects of the educational system, support system, learner quality, instructor quality, and information quality. PSSUQ method is used for 4 assessment categories with a 7-point Likert scale assessment of the technology usability concept. Meanwhile, the Naive Bayes method is used to analyse the polarity of comments related to the effectiveness of IT utilization in the online learning process. The results obtained from research on students of the Department of Information Systems class of 2018 and 2019, obtained 18 subcategories successfully exceeded the target with a score of 5.18. The ease to learn and ease to use subcategories have the highest average score of 6.30, while the previous experience subcategory has the lowest average score of 5.18. The ease to learn and ease to use subcategories have the highest average score of 6.30, while the previous experience subcategory has the lowest average score of 5.26. For processing the polarity of comments regarding the ease to use subcategory, a positive sentiment of 90.3% was obtained, visualized using a word cloud. The results of this study show that out of 24 subcategories of assessment aspects, only 1 is still below the average target and the utilization of IT in the online learning process meets its utilization objectives. The resulting evaluation instrument can be utilized as part of a sustainable quality assurance process.